Subsurface Structure at the InSight Landing Site From Compliance Measurements by Seismic and Meteorological Experiments. Issue 6 (15th June 2020) - Kenda, B.; Drilleau, M.; Garcia, R. F.; Kawamura, T.; Murdoch, N.; Compaire, N.; Lognonné, P.; Spiga, A.; Widmer‐Schnidrig, R.; Delage, P.; Ansan, V.; Vrettos, C.; et al.
Abstract: Measurements of ground compliance at the InSight landing site—describing the surface response to pressure loading—are obtained from seismic and meteorological data. Compliance observations show an increase with frequency indicating the presence of a stiffer rock layer beneath the exposed regolith. We performed a Markov chain Monte Carlo inversion to investigate the vertical profile of the elastic parameters down to 20 m below InSight. Compliance was inverted both freely and assuming prior knowledge of compaction in the regolith, and the limitations and strengths of the methods were assessed on the basis of theoretical considerations and synthetic tests. The inverted Young modulus exhibits an increase by a factor of 10–100 over the first 10–15 m, compatible with a structural discontinuity between 0.7 and 7 m. The proposed scheme can be used for joint inversion of other seismic, geological, or mechanical constraints to refine the resulting vertical section. Plain Language Summary: Pressure fluctuations of the Mars' atmosphere induce tiny deformations of the ground that can be measured by the very sensitive seismometer of the InSight mission. The amount of deformation depends on the elastic properties of the sandy regolith (the surface layer exposed and highly fractured by impacts) and of the underlying rocks and can thus be used to explore beneath the surface. In this work, we review the theory describing the ground motion caused by moving pressure perturbations, and we analyze the effect of various parameters (wind speed and layering in the subsurface). We then develop a method to retrieve a vertical profile of the elastic parameters beneath the lander from the measurements. After testing the method on ideal cases, we apply it to data from Mars: The results show that the regolith becomes stiffer with depth and that a layer of harder rock may be present below, with the interface possibly located between 0.7 and 7 depth. Determining the structure of the near surface provides constraints on the geologic history of the landing site and contributes to the explanation of measured seismic signals. Key Points: Ground compliance measurements by InSight depend on the elastic properties in the near surface of Mars Observed compliance from convective vortex encounters and other pressure fluctuations opens the way to the exploration of the near surface Markov chain Monte Carlo inversion for the Young modulus profile suggests stratification within and below the regolith